Intention to stay of generation Y government officer in the Revenue Department: the mediating role of employee engagement: Intention to stay of generation Y government officer in the Revenue Department: the mediating role of employee engagement - Johkhao, Phornpailin; Akkawanitcha, Chuanchuen (RATANABUTH JOURNAL, 2023)
This study aims to study the factors affecting to Intention to stay and the mediating role of employee engagement on the effects of financial compensation, career growth opportunities, work life balance on intention to stay of generation Y government officer in the Revenue Department. The sample are 377 of government officer in the Revenue Department who are generation Y. The questionnaire is employed as research instrument. Data is analyzed by the structural equation model (SEM). The results showed that the level of the satisfaction in financial compensation is low level while career growth opportunities, work life balance, employee engagement and intention to stay are high level. The hypothesis tests had been found that financial compensation, career growth opportunities and work life balance have a positive influence on employee engagement, employee engagement have a positive influence on intention to stay. the mediation results show full mediation of employee engagement on the effects of financial compensation, career growth opportunities, work life balance on intention to stay.